Modelling the influence of ectomycorrhizal decomposition on plant nutrition and soil carbon sequestration in boreal forest ecosystems - Baskaran, Preetisri (The New phytologist, 2017)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.